The Science-Music Borderlands (The MIT Press, 2023)
Interdisciplinary essays on music psychology that integrate scientific, humanistic, and artistic ways of knowing in transformative ways.Researchers using scientific methods and approaches to advance our understanding of music and musicality have not yet grappled with some of the perils that humanistic fields concentrating on music have long articulated. In this edited volume, established and emerging researchers—neuroscientists and cognitive scientists, musicians, historical musicologists, and ethnomusicologists—build bridges between humanistic and scientific approaches to music studies, particularly music psychology. Deftly edited by Elizabeth H. Margulis, Psyche Loui, and Deirdre Loughridge, The Science-Music Borderlands embodies how sustained interaction among disciplines can lead to a richer understanding of musical life.The essays in this volume provide the scientific study of music with its first major reckoning, exploring the intellectual history of the field and its central debates, while charting a path forward. The Science-Music Borderlands is essential reading for music scholars from any disciplinary background. It will also interest those working at the intersection of music and science, such as music teachers, performers, composers, and music therapists.Contributors:Manuel Anglada-Tort, Salwa El-Sawan Castelo-Branco, Hu Chuan-Peng, Laura K. Cirelli, Alexander W. Cowan, Jonathan De Souza, Diana Deutsch, Diandra Duengen, Sarah Faber, Steven Feld, Shinya Fujii, Assal Habibi, Erin. E. Hannon, Shantala Hegde, Beatriz Ilari, Jason Jabbour, Nori Jacoby, Haley E. Kragness, Grace Leslie, Casey Lew-Williams, Deirdre Loughridge, Psyche Loui, Diana Mangalagiu, Elizabeth H. Margulis, Randy McIntosh, Rita McNamara, Eduardo Reck Miranda, Daniel Müllensiefen, Rachel Mundy, Florence Ewomazino Nweke, Patricia Opondo, Aniruddh D. Patel, Andrea Ravignani, Carmel Raz, Matthew Sachs, Marianne Sarfati, Patrick E. Savage, Huib Schippers, Jim Sykes, Gary Tomlinson, Jamal Williams, Maria A. G. Witek, Pamela Z